2016
DOI: 10.1371/journal.pone.0156362
|View full text |Cite
|
Sign up to set email alerts
|

Global Synthesis of Drought Effects on Maize and Wheat Production

Abstract: Drought has been a major cause of agricultural disaster, yet how it affects the vulnerability of maize and wheat production in combination with several co-varying factors (i.e., phenological phases, agro-climatic regions, soil texture) remains unclear. Using a data synthesis approach, this study aims to better characterize the effects of those co-varying factors with drought and to provide critical information on minimizing yield loss. We collected data from peer-reviewed publications between 1980 and 2015 whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
405
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 716 publications
(429 citation statements)
references
References 49 publications
14
405
0
10
Order By: Relevance
“…2b). Maize, in particular, was sensitive to drought during the reproductive phase, to the point that yield could not be recovered even with subsequent irrigation due to flower sterility and asynchrony between anthesis and silking (Daryanto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2b). Maize, in particular, was sensitive to drought during the reproductive phase, to the point that yield could not be recovered even with subsequent irrigation due to flower sterility and asynchrony between anthesis and silking (Daryanto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between irrigation and rainfall ranged between 0.3 and 4.9. If a study was conducted across different years or study sites with similar agro-ecological features, or reported more than one amount of irrigation, all observations were considered independent and included in the database (Daryanto et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L; 2n=6x=42, AABBDD) production and productivity is challenged by periodic drought and heat stresses associated with climate change (Alexandratos and Bruinsma, 2012;Daryanto et al, 2016). A decreasing trend is witnessed in the total production area and productivity of wheat and other long cycle cereal crops under dryland production conditions globally (Simelton et al, 2012;Lesk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The biotic stress reduces growth, yield and modifies the morphological and physiological attributes in subjected plants [5]. Reduced dry matter production has been observed in plants under stress [6].…”
Section: Introductionmentioning
confidence: 99%